Pat‐geom: A software package for the analysis of animal patterns. Issue 4 (10th January 2019) - Chan, Ian Z. W.; Stevens, Martin; Todd, Peter A.
Abstract: Colour patterns often influence how animals interact with one another, but the ability of researchers to quantify pattern per se is hampered by a lack of easily accessible and user‐friendly measurement software packages. We address this issue by releasing pat‐geom, a free software package for use within ImageJ that allows users to measure seven properties of a pattern: (a) the shape of its markings, (b) the directionality in the shape of its markings, (c) the size of its markings, (d) the contrast of the pattern, (e) the distribution of its markings, (f) the directionality in the distribution of its markings, and (g) the randomness of the pattern. We provide examples of how pat‐geom may be used, such as to visualise the "average pattern" of a population of animals, or to compare the patterns on two animals. Using data from two case studies, we also demonstrate pat‐geom 's ability to identify the specific aspects of an organism's pattern that match its background and to design artificial prey items that accurately resemble their model organism for use in predation experiments. pat‐geom collates the tools to measure these seven diverse properties of animal colour patterns into one convenient, easy‐to‐use package. It can be employed in a wide range of studies on topics such as aposematism, camouflage and mimicry, and also has the potential to be applied to other research fields such as landscape ecology, botany and cellular biology.